Antibacterial potential of robusta coffee beans (Coffea canephora var. robusta): A review - Anis Irmawati; Salsabila Nurmalia; Annisa Rahmaputri; Nurul Mahmudati; Labib Noman; Noor Faizah Balqis (Faculty of Dental Medicine Universitas Airlangga, 2026)
Background: A gram-positive bacterium, Staphylococcus aureus, is known for causing infections in areas like the skin, lungs, and mouth, and has spurred interest in natural remedies due to growing antibiotic resistance. This has led researchers to explore alternatives from sources such as Robusta coffee beans (Coffea canephora var. robusta), which contain potent bioactive substances. Purpose: The review aims to elaborate on the effectiveness of Robusta coffee beans in combating pathogens like S. aureus and to pinpoint the key ingredients contributing to their antibacterial activity. Reviews: Research indicates that Robusta coffee beans are rich in active elements (caffeine, chlorogenic acid, caffeic acid, and trigonelline), all of which demonstrate antimicrobial and antivirulence capabilities. These compounds work by compromising the integrity of the bacterial cell membrane, blocking protein production, and weakening the cell wall, ultimately resulting in cell breakdown. Chlorogenic acid, the most abundant of these, shows both inhibitory and lethal effects on bacteria. S. aureus is notorious for building tolerance to multiple antibiotics, complicating treatment. This challenge stems from its harmful traits, notably Panton-Valentine Leukocidin (PVL), which boosts its danger by destroying leukocytes and triggering tissue necrosis. Conclusion: Robusta coffee beans (C. canephora var. robusta) have great potential antibacterial activity attributed to their bioactive compounds, which inhibit pathogens such as S. aureus, Escherichia coli, Staphylococcus epidermidis, and Salmonella typhi. These findings suggest that robusta coffee beans may serve as a viable source for developing alternative natural antibacterial formulations, particularly against S. aureus associated infections.